Pengaruh Servant Leadership Style, Komunikasi Interpesonal Terhadap Kinerja Karyawan Pada PT. Socfindo Aek Pamienke Kabupaten Labuhanbatu Utara - Ali Sahputra (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to determine the influence of servant leadership style,interpersonal communication on employee performance at PT. Socfindo AEK Pamienke North Labuhan Batu Regency.The data collection method used through the survey approach with the type of quantitative descriptive research questionnaire spread to 50 respondents, while the population in this study are employees in the factory division precisely in the field of plant operators. Data collection techniques through interviews, questionnaires and documentation studies. Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and coefficient of determination test (R2) and path analysis using SPSS (Statistical Product Software Solution).The results showed simultaneously variable servant leadership style significant influence on employee performance F count 40,302 > F Table 2.579 with a significant value of 0.000 < 0.05, partially servant leadership style positive and significant influence on employee performance obtained value thitung 3.884 > ttable 1.679 and the probability value of t is 0.001 < 0.05, partially interpesonal communication positive and significant effect on employee performance obtained value thitung 4.161 > ttable 1.679 and the probability value of t is 0.000 < 0.05.